Review of preparation and application of copper–steel bimetal composites. Issue 4 (16th September 2019) - Wang, Yiran; Gao, Yimin; Li, Yefei; Zhai, Wenyan; Sun, Liang; Zhang, Chao
Abstract : With the rapid development of modern science and industrial technology, single metals or alloys are restricted by working conditions and cost. It is challenging to meet the requirements for current applications. Copper (Cu)–steel bimetal composites, composed of copper and steel, have performances of the two metals and low cost. They have drawn extensive attention worldwide and have been developed by many scholars for many years. The new preparations are studies to promote performances of the copper–steel bimetal composites and many literatures have also reported different applications of the copper–steel bimetal composites. Up to today, the developing copper–steel bimetal composites have made a great progress. This paper is mainly concerned with the progress of research on the preparation of copper–steel bimetal composites. The preparations are classified according to the forming state of copper and steel. Furthermore, the industrial applications of copper–steel bimetal composites and the prospects of future development are introduced.